FEATURES OF EARLY DIAGNOSIS OF HURTICAL - Minavara Ulugbekovna Tursunova; Mirzahid Sabitjanovich Musakov; Durdona Akbaraliyevna Raimova (Scholars Digest Publishing, 2024)
Urticaria is a group of diseases characterized by the development of itchy blisters and/or angioedema [1]. In approximately 40% of cases, urticaria is accompanied by angioedema. The prevalence of acute urticaria ranges from 1 to 5% in the population, and among the pediatric population, the incidence of acute urticaria reaches 6.7%. Recent estimates suggest that 10 to 20% of the population will experience an episode of acute urticaria during their lifetime. About 50% of children with acute urticaria have concomitant allergic diseases [2]. According to S. Comert, the most common triggers of acute urticaria are drugs (38.1%), infections (35.2%), stress (24.7%) and food (17.8%) [7]. In another study, drugs were also the most common cause of acute urticaria - 20.7%; the next most common were insect bites (10.2%) and food products (7.4%) [3].
Keywords: urticaria, diagnosis, treatment, effectiveness, safety, acute allergic-pseudoallergic reactions, provoking factors, food allergy, drug allergy, urticaria, angioedema.